ACTH-Independent Cushing’s Syndrome with Bilateral Micronodular Adrenal Hyperplasia and Ectopic Adrenocortical Adenoma - Louiset, Estelle (The Endocrine Society, 2010)
Context: Bilateral micronodular adrenal hyperplasia and ectopic adrenocortical adenoma are two rare causes of ACTH-independent Cushing’s syndrome. Objective: The aim of the study was to evaluate a 35-yr-old woman with ACTH-independent hypercortisolism associated with both micronodular adrenal hyperplasia and ectopic pararenal adrenocortical adenoma. Design and Setting: In vivo and in vitro studies were performed in a University Hospital Department and academic research laboratories. Intervention: Mutations of the PRKAR1A, PDE8B, and PDE11A genes were searched for in leukocytes and adrenocortical tissues. The ability of adrenal and adenoma tissues to synthesize cortisol was investigated by immunohistochemistry, quantitative PCR, and/or cell culture studies. Main Outcome Measure: Detection of 17α-hydroxylase and 21-hydroxylase immunoreactivities, quantification of CYP11B1 mRNA in adrenal and adenoma tissues, and measurement of cortisol levels in supernatants by radioimmunological assays were the main outcomes. Results: Histological examination of the adrenals revealed nonpigmented micronodular cortical hyperplasia associated with relative atrophy of internodular cortex. No genomic and/or somatic adrenal mutations of the PRKAR1A, PDE8B, and PDE11A genes were detected. 17α-Hydroxylase and 21-hydroxylase immunoreactivities as well as CYP11B1 mRNA were detected in adrenal and adenoma tissues. ACTH and dexamethasone activated cortisol secretion from adenoma cells. The stimulatory action of dexamethasone was mediated by a nongenomic effect involving the protein kinase A pathway. Conclusion: This case suggests that unknown molecular defects can favor both micronodular adrenal hyperplasia and ectopic adrenocortical adenoma associated with Cushing’s syndrome.